Monopoly with Resale - Giacomo Calzolari; Alessandro Pavan (Fondazione Eni Enrico Mattei (FEEM), 2003)
This paper studies revenue-maximizing mechanisms for a monopolist who expects her buyers to resell in a secondary market. We consider two modes of resale: the first is to a third party who does not participate in the primary market; the second is inter-bidders resale, where the winner in the primary market resells to the losers. We show that resale to third parties is revenue-enhancing for the initial monopolist, whereas inter-bidders resale is revenue-decreasing compared to the case where resale is prohibited. The revenue-maximizing mechanisms in the primary market are obtained by investigating the optimal informational linkage with the secondary market. The results show that to sustain higher resale prices the monopolist may find it optimal (a) to induce stochastic allocations in the primary market, and (b) to design a disclosure policy that optimally controls for the information revealed to the participants in the secondary market. The optimal allocation rule and disclosure policy maximize the expected sum of the bidders' resale-augmented virtual valuations, taking into account the effect of information disclosure on the price formation process in the secondary market.
Keywords: D44; D82; 330; Monopoly; information linkage between primary and secondary markets; optimal auction with resale; resale-augmented virtual valuations; Monopol; Auktionstheorie; Dynamisches Spiel; Unvollkommene Information; Theorie